Show me the skin! Does seeing the back enhance tactile acuity at the back? - Catley, M; Tabor, A; Miegel, R; Wand, B; Spence, C; Moseley, G (Elsevier, 2014)
A growing body of literature associates musculoskeletal disorders with cortical reorganisation. One condition in which reorganisation is established and treatments that 'train the brain' are being widely used is chronic back pain. Recent evidence suggests that treatments that involve tactile training are more effective if they incorporate multisensory mechanisms, most obviously vision. With regard to back pain however, we must first determine if tactile function is enhanced by incorporating other modalities. A series of three cross-over experiments were conducted in healthy pain-free subjects to determine whether tactile acuity is enhanced when participants can see the skin of their back during testing. An initial randomised cross-over experiment suggested tactile acuity was significantly enhanced when participants could see their backs (t(25) = -4.226, p < 0.001, r = 0.65). However, a second replication experiment was not corroborative. Both the second (F(3,66) = 1.00, p = 0.398) and third (t(9) = 0.969, p = 0.358) experiments suggested that seeing the back did not significantly affect tactile acuity, confirming that our initial results were likely due to chance. The principle that visual feedback improves tactile acuity at the hand does not apply to the back. These results strongly suggest that attempts to enhance tactile training by incorporating vision will not offer the benefit to treatment of back pain that has been observed for treatment of hand pain.